The effects of solid barriers and blocks on the propagation of smoke within longitudinally ventilated tunnels. (August 2019) - Chaabat, F.; Creyssels, M.; Mos, A.; Wingrave, J.; Correia, H.; Marro, M.; Salizzoni, P.
Abstract: A series of experiments were conducted to investigate the effect of solid barriers, placed at the tunnel ceiling, on the behaviour of smoke in fire events within longitudinally ventilated tunnels, namely on the smoke back-layering lengths and on the critical velocity. For this purpose, we considered two types of barrier: "small barriers" designed to be fixed in place and "large barriers" designed to be mobile in real tunnels. The study was carried out in a small scale tunnel, by simulating fire smokes with a light gas mixture of air and helium. Experiments were performed with and without blocks within the tunnel, representing vehicles. Results show that the presence of barriers and/or blocks prevents the smoke back-layering flow, therefore reducing the critical velocity. The reduction rate of the latter depends on the blocking rate created by the obstacles (barriers, blocks or both) located just upstream of the source. Further experiments were conducted to investigate the effects of blockages on pressure losses inside the tunnel. The results reveal a proportionality between head losses and height of barriers, and between pressure drops and size of the blocks.When both blocks and barriers are present, the pressure losses induced by the small barriers are very high compared to those induced by the large barriers, especially in the tunnel with large blocks. These findings suggest that large barriers are more effective than small ones because they prevent the smoke back-layering at very low critical velocities and they induce less pressure losses in congested tunnels. Highlights: The barriers prevent the back-layer flow from moving upstream of the source. The effectiveness of the barrier depends on its height. The simultaneous presence of blocks and barriers in the tunnel increase the pressure losses. Pressure losses induced by small barriers are much greater than those induced by the large barriers. Large barriers present an important means to improve the safety in road tunnels.